Development of e-Handout based on Discovery Learning for Respiratory System Material - Taqiya, Nurul Rifqi; Oprasmani, Elfa; Nevrita, Nevrita (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2023)
Motivated by the needs of students for teaching materials on Respiratory System material, the researcher decided to develop teaching material in the form of electronic handout to support the learning of Respiratory System material. This study aims to produce an e-Handout based on Discovery Learning for Respiratory System Material that is valid, practical, and effective. This research uses a 4D development model with four stages, namely define, design, develop, and disseminate. Based on the results of the media and material validity test of e-Handout based on Discovery Learning for Respiratory System Material, the results were very valid. The results of the practicality of media get results with the criteria very practical. The media effectiveness assessment received the very effective criterion with an average classical completion of 86.6%. Based on the results of the research obtained, it can be concluded that the e-Handout based on Discovery Learning for Respiratory System Material is declared valid, practical, and effective for use in learning Biology of Respiratory System material. The developed e-Handout is packaged in a pre-existing form and can be used for independent learning. This research is expected to be a reference for other researchers who will develop similar products on other Biology materials.